A Novel Therapy for cocaine dependence during abstinence: A randomized clinical trial - Pirnia, Bijan (Electron Physician, 2017)
BACKGROUND: Topiramate is an anticonvulsant drug and an ideal candidate for reducing the craving in people relying on cocaine. Contingency management is one of the common therapies in the domain of addiction. OBJECTIVE: The present study aimed to evaluate and compare three medication methods of Topiramate (TPM), Contingency Management (CM) and the combined TPM treatment and cash intervention on craving during abstinence. METHODS: This randomized clinical trial was conducted at Bijan Center for Substance Abuse Treatment in Tehran, Iran, from December 15, 2014 to November 20, 2015. One hundred males (Age range=18–34; SD=4.11) undergoing abstinence were assigned randomly to four groups (n=25) of Topiramate (TPM), Contingency Management (CM) and the Combined Method plus a placebo control group. Treatment was provided for twelve weeks for the experiment groups, and only the control group received the placebo. Participants in the Cash-based and CM Condition had an identical 12-week escalating schedule of reinforcement (cash-based incentives worth $0, $20, $40, and $80). Also, in the Topiramate group, participants’ dosage ranged between 25–300 mg/day in escalating doses) 25, 50, 100, 150, 200, 250, 300). In addition, all subjects received brief behavioral compliance enhancement treatment (BBCET). Participants took a urine test twice a week, with a given threshold of > 300 ng/ml, and indicators of cocaine craving (response rate= 91%) was evaluated in two phases of pre-test and post-test. We used Chi square, ANCOVA Univariate Model and Scheffe’s post hoc to analyze the primary and secondary outcomes. Also, the qualitative data resulted from demographic evaluations were coded and analyzed by the instrument of analysis of qualitative data i.e. Atlas.ti, Version 5.2. RESULTS: The results showed that all three types of treatment played a significant efficacy in reducing the craving. The mean (95% CI) scores of craving was 12.04 (p=0.05) with TPM, 13.89 (p=0.05) with CM, 10.92 (p=0.01) with Mix and 16.89 (p>0.05) with control. Moreover, the highest variance explaining the changes in craving was assigned to the combined treatment (p<0.01). CONCLUSIONS: The findings of this study, while having applicable aspects in this domain, can be helpful in planning supplementary remedial procedures. TRIAL REGISTRATION: The trial was registered at the Thai Clinical Trial Registration Center with the TCR ID: TCTR20170112001. FUNDING: The authors received no financial support for the research, authorship, and/or publication of this article.